The isolated warrior: the impact of everyday forms of individual public servants’ resistance on new public management reforms in sri lanka - Hettiarachchi, T.N. (University of Jaffna, 2012)
This study analyses the impact of the everyday forms of resistance performed by individual public servants following the implementation of New Public Management (NPM) reforms in Sri Lanka. Many elements of the NPM reforms, such as productivity improvement and performance targets affect individual public servants in a highly personalized nature. For this reason they are unable to garner the widespread support required to prompt collective action as form of resistance. This study argues that this highly personalized nature of reforms pushes individual public servants to adopt everyday forms of resistance, which eventually make a cumulative impact on the reforms. The conceptual framework developed by James C. Scott to analyze the everyday forms of peasant resistance is used in this study to infer a model of the public servants’ everyday forms of resistance. Analyzing stories of individual public servants who were accused of being resisters, this paper reveals the nature and limitations of the everyday forms of resistance that public servants have adopted as well as their impact on the NPM reforms.